Detecting mechanical breakpoints during treadmill-based graded exercise test: Relationships to ventilatory thresholds. Issue 7 (3rd July 2022) - Li, Siu Nam; Peeling, Peter; Hansen, Clint; Van Alsenoy, Ken; Ryu, Joong Hyun; Girard, Olivier
ABSTRACT: Background: While changes in cardio-respiratory variables during graded exercise tests (GXTs) are well described, less is known about running mechanical alterations. Purpose: We determined mechanical breakpoints during GXT and compared their temporal location with thresholds in ventilation. Methods: Thirty-one recreational male runners completed continuous GXT on an instrumented treadmill, starting at 2.5 m.s −1 with velocity increases of +0.14 m.s −1 every 30 s. Subsequently, the first and second ventilatory thresholds (VT1 and VT2) were determined from expired gases. Spatio-temporal and antero-posterior force variables, and spring-mass model characteristics were averaged for each stage. Mechanical breakpoints were detected using a linear fit process that partitioned the timeseries into two regions and minimised the error sum of squares. All measurements were normalised to % GXT duration for subsequent comparisons. Results: Fifteen out of 16 mechanical variables (all except leg stiffness) displayed breakpoints occurring between 61.9% and 82.3% of GXT duration; these occurred significantly later than VT1 (46.9 ± 6.4% of GXT duration, p  < .05). Mechanical breakpoints for eight variables (step frequency, aerial time, step length, peak push-off force, braking impulse, peak vertical force, maximal downward vertical displacement and leg compression) occurred at a time point not different to VT2 (75.3 ± 6.2% of GXT duration; all p  > .05). Relationships between mechanical breakpoints and either VT1 or VT2 were weak (all r  < 0.25). Conclusion: During treadmill GXT, breakpoints can be detected for the vast majority of mechanical variables (except leg stiffness), yet these are not related with ventilatory thresholds.